Protocol for a nationwide prospective, observational cohort study of foreign-body airway obstruction in Japan: the MOCHI registry. Issue 7 (20th July 2020) - Norii, Tatsuya; Igarashi, Yutaka; Sung-Ho, Kim; Nagata, Shimpei; Tagami, Takashi; Yoshino, Yudai; Hamaguchi, Takuro; Maejima, Riko; Nakao, Shunichiro; Albright, Danielle; Yokobori, Shoji; Yokota, Hiroyuki; et al.
Abstract : Introduction: Foreign body airway obstruction (FBAO) is a major public health issue worldwide. In 2017, there were more than 5000 fatal choking cases in the USA alone, and it was the fourth leading cause of preventable injury-related death in the home and community. In Japan, FBAO is the leading cause of accidental death and with almost 9000 fatalities annually. However, research on FBAO is limited, particularly on the impact of a foreign body (FB) removal manoeuvres by bystanders. The primary objective of this study is to determine the impact of bystander FB removal manoeuvres on 1 month neurological outcome. Our secondary objectives include (1) evaluating the efficacy of a variety of FB removal manoeuvres; (2) identifying risk factors for unsuccessful removal and (3) evaluating the impact of time intervals from incidents of FBAO to FB removal on neurological outcome. Methods and analysis: We will conduct a nationwide multi-centre prospective cohort study of patients with FBAO who present to approximately 100 emergency departments in both urban and rural areas in Japan. Research personnel at each participating site will collect variables including patient demographics, type of FB and prehospital variables, such as bystander FB removal manoeuvres, medical interventions by prehospital personnel, advanced airway management and diagnostic findings. Our primary outcome is 1 month favourable neurological outcome defined as cerebral performance category 1 or 2. Our secondary outcomes include success of FB removal manoeuvres and complications from the manoeuvres. We hypothesise that bystander FB removal manoeuvres improve patient survival with a favourable neurological outcome. Ethics and dissemination: This study received research ethics approval from Nippon Medical School Hospital (B-2019-019). Research ethics approval will be obtained from all participating sites before entering patients into the registry. The study was registered at the University Hospital Medical Information Network (UMIN) Clinical Trials Registry. Trial registration number: UMIN 000039907.